Chemical process equipment : selection and design - Walas, Stanley M. (Butterworth-Heinemann, 1990)
Chemical Process Equipment is a guide to the selection and design of a wide range of chemical process equipment. Emphasis is placed on specific information concerning the process design and performance of equipment. To this end, attention is given to examples of successful applications, and a number of line sketches showing the functioning of equipment is included with many graphs and tables giving their actual performance. For coherence, brief reviews of pertinent theory, including numerical examples to illustrate the more involved procedures, are provided.
Previously published: Boston : Butterworths, ©1988. (Butterworths series in chemical engineering).
Keywords: Chemical engineering -- Equipment and supplies.; elektronické knihy; electronic books